Association between Screentime and it’s Behavioral, Psychological and Physical health impacts in Children, Adolescents, Adults: A multi- age cross-sectional study - Dr. Shravan Kumar Dholi; Heeba Saqmi; Khaja Abdul Aziz; V. Ramesh; Kusuma Vaishnavi (Asian Journal of Pharmaceutical Research and Development, 2026)
Background: Across all age groups, excessive screen usage has been linked to poor sleep and mental health outcomes. Goal: To assess how screen usage affects kids, teens, and grown-up’s behavioural, emotional, sleep, anxiety, and depressive outcomes. Methodology: A standardized questionnaire was used in a cross-sectional observational study to measure electronic media engagement patterns in 300 study participations. Adults were evaluated using PSQI, GAD-7, and PHQ-9, while children and adolescents' behavioural and emotional outcomes were analysed using PMUM/PMUM-SF and SDQ. Statistical analysis was used to examine relationships between device usage time and outcome measures. Results: Increased time spent on display (≥4 hours) was linked to worse sleep (66%), as well as more feelings of severe anxiety (7%) and severe depression (8%) in adults. Increased media use was linked to more emotional, behavioural, and peer issues in children and teenagers. Worsening mental health outcomes were strongly correlated with poor sleep quality, indicating a mediation function. Conclusion: Across all age groups, increased screen usage is strongly linked to poor sleep and mental health outcomes. Psychological and sleep-related morbidity may be avoided with early detection and public health initiatives that encourage responsible technology use.